Meningkatkan Aktivitas dan Keterampilan Berpikir Kritis Menggunakan Model CANGKAL di SDN Sungai Miai 11 Banjarmasin - Rennie Fahlia Putri; Noorhapizah . (CV. ITTC INDONESIA, 2024)
The problem discussed is the lack of activity and low critical thinking skills in students. The cause is the internal factor of students who lack confidence in their abilities and are afraid of making mistakes. One of the solutions provided to overcome this problem is to apply learning using the CANGKAL model. This research was conducted with the aim of analyzing students' critical thinking activities and skills. This research used a qualitative method with a type of PTK which was carried out in 4 meetings. The research subjects consisted of 12 class IV A students at SDN Sungai Miai 11 Banjarmasin in the second semester of the 2023/2024 academic year. The results showed that there was an increase in students' activity and critical thinking skills, reaching 92% at the 4th meeting. Based on these findings, it can be concluded that the use of the CANGKAL model is effective in increasing students' critical thinking activities and skills. These findings can also be used as a guide in developing learning models to improve the quality of learning